Method for producing solid electrolytes

JP2026167149APending Publication Date: 2026-10-14NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025060569
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本発明によれば水蒸気雰囲気下で焼成工程が行われるため、固相反応が促進され、立方晶の割合を大きくできる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167149000001_ABST
    Figure 2026167149000001_ABST
Patent Text Reader

Abstract

This invention provides a method for producing solid electrolytes that allows for a high proportion of cubic crystals. [Solution] The method for producing a solid electrolyte includes a calcination step in which a solid electrolyte having a garnet-type crystalline structure containing Li, La, Zr, and O is synthesized, and the calcination step is carried out under a water vapor atmosphere. The raw material powder used to synthesize the solid electrolyte in the calcination step preferably contains lithium carbonate and lanthanum hydroxide, and the specific surface area of ​​lithium carbonate is 0.10 m². 2 The value is 1 / g or more, and the specific surface area of ​​lanthanum hydroxide is 3.0 m². 2 It is more preferable if it is 1 / g or more.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a method for producing a solid electrolyte having a garnet-type crystal structure containing Li, La, Zr and O. BACKGROUND ART

[0002] Patent Document 1 discloses a prior art in which powders each containing Li, La and Zr are mixed in dehumidified gas, and the resulting mixture is fired, in order to produce a solid electrolyte having a garnet-type crystal structure containing Li, La, Zr and O. PRIOR ART DOCUMENTS PATENT DOCUMENTS

[0003] PATENT DOCUMENT 1 Japanese Unexamined Patent Application Publication No. 2019-6634 SUMMARY OF INVENTION PROBLEM TO BE SOLVED BY THE INVENTION

[0004] In the prior art, a technique for increasing the proportion of garnet-type cubic crystals has been demanded.

[0005] The present invention has been made to meet this demand, and an object thereof is to provide a method for producing a solid electrolyte that can increase the proportion of cubic crystals. MEANS FOR SOLVING THE PROBLEM

[0006] A first aspect for achieving this object is a method for producing a solid electrolyte, including a firing step of synthesizing a solid electrolyte having a garnet-type crystal structure containing Li, La, Zr and O, wherein the firing step is performed in a water vapor atmosphere.

[0007] In a second aspect based on the first aspect, the raw material powder for synthesizing the solid electrolyte in the firing step contains lithium carbonate and lanthanum hydroxide.

[0008] In the third embodiment, in the second embodiment, the specific surface area of ​​lithium carbonate is 0.10 m². 2 The value is 1 / g or more, and the specific surface area of ​​lanthanum hydroxide is 3.0 m². 2 It is 1 / g or more.

[0009] The fourth aspect is that, in any of the first to third aspects, the raw material powder used to synthesize the solid electrolyte in the calcination process contains zirconium oxide, and the specific surface area of ​​the zirconium oxide is 10.0 m². 2 It is 1 / g or more. [Effects of the Invention]

[0010] According to the present invention, since the firing process is carried out in a steam atmosphere, the solid-phase reaction is promoted, and the proportion of cubic crystals can be increased. [Brief explanation of the drawing]

[0011] [Figure 1] This is a schematic diagram of the firing process in the first embodiment. [Figure 2] This is a schematic diagram showing the crystal structure of a garnet-type crystal. [Figure 3] This is a schematic diagram of the firing process in the second embodiment. [Modes for carrying out the invention]

[0012] Preferred embodiments of the present invention will be described below with reference to the accompanying drawings. Figure 1 is a schematic diagram of the firing process in the first embodiment. The firing process is a process of firing the raw material powder 10 of the solid electrolyte in a furnace (not shown). In this embodiment, the raw material powder 10 is contained in a firing jig 12 placed on the base plate 11 of the furnace.

[0013] Examples of furnaces include a continuous firing furnace in which a base plate 11 moves within a heating zone (not shown) to transport the firing jig 12, and a batch firing furnace in which the base plate 11 is fixed to the furnace and the temperature around the firing jig 12 changes. Examples of continuous firing furnaces include roller hearth kilns, pusher kilns, tunnel kilns, walking beam furnaces, and mesh belt furnaces. In the case of a mesh belt furnace, the base plate 11 may be omitted, and the firing jig 12 may be transported by placing it directly on the mesh belt.

[0014] The raw material powder 10 is exemplified by a mixture of various metal salts such as oxides, hydroxides, and carbonates containing Li, La, and Zr. There are no restrictions on the raw material powder containing Li, but lithium carbonate, lithium hydroxide, and lithium nitrate are examples. These can be used individually or two or more can be combined in any ratio. Among these, lithium carbonate is preferred because it is easy to handle. To increase reactivity, the specific surface area of ​​lithium carbonate is 0.10 m². 2 A value of / g or more is preferable.

[0015] Examples of raw material powders containing lanthanum include lanthanum hydroxide and lanthanum oxide. These can be used individually or in combination of two or more in any ratio. Among these, lanthanum hydroxide is preferred due to its ease of handling. To enhance reactivity, the specific surface area of ​​lanthanum hydroxide is 3.0 m². 2 A value of / g or more is preferable.

[0016] Examples of raw material powders containing Zr include zirconium oxide and zirconium hydroxide. These can be used individually or in combination of two or more in any ratio. Among these, zirconium oxide is preferred because it is easy to handle. To enhance reactivity, the specific surface area of ​​zirconium oxide is 10.0 m². 2 A value of / g or more is preferable.

[0017] The solid electrolyte synthesized by calcining the raw material powder 10 is an oxide having a garnet-type crystal structure. The crystal structure of a garnet-type oxide is given by the general formula C3A2B3O 12 It is represented as follows.

[0018] Figure 2 is a diagram schematically illustrating a garnet-type crystal structure. In the garnet-type crystal structure, the C-site Sc is in dodecahedral coordination with oxygen atoms Oa, the A-site Sa is in octahedral coordination with oxygen atoms Oa, and the B-site Sb is in tetrahedral coordination with oxygen atoms Oa. In the garnet-type crystal structure, Li can be present at positions that are octahedrally coordinated with oxygen atoms Oa and serve as voids V. The void V is, for example, a position sandwiched between the B-site Sb1 and the B-site Sb2. Li present in the void V is in octahedral coordination with oxygen atoms Oa that form an octahedron including the face Fb1 of the tetrahedron forming B-site Sb1 and the face Fb2 of the tetrahedron forming B-site Sb2.

[0019] For example, Li7La3Zr2O 12 In the garnet-type solid electrolyte having the composition of, La can occupy the C-site Sc, Zr can occupy the A-site Sa, and Li can occupy the B-site Sb and the void V. The garnet-type solid electrolyte has an X-ray diffraction file No. 422259 (Li7La3Zr2O) from the CSD (Cambridge Structural Database) 12 has an XRD pattern similar to that of.

[0020] Various elements are substituted in the garnet-type solid electrolyte. For example, Ca, Sr, Ba, etc. substitute at the C-site, Nb, Ta, Sn, Hf, etc. substitute at the A-site, and Al, Ga, etc. substitute at the B-site. The amount of lithium changes due to element substitution, and the ionic conductivity changes as the arrangement, occupancy rate, and occupied sites of lithium ions in the crystal structure change. The diffraction angle and intensity ratio may differ from those of No. 422259 due to element substitution.

[0021] Li7La3Zr2O 12 may have a part of its constituent elements substituted with other elements, or a trace amount of other elements may be added without substituting the constituent elements. Examples of the other elements include at least one element selected from the group consisting of Mg, Al, Si, Ca, Ti, V, Ga, Sr, Y, Nb, Sn, Sb, Ba, Hf, Ta, W, Bi, Rb, and lanthanoids (excluding La).

[0022] For example, Li6La3Zr 1.5 W 0.5 O 12 , Li 6.15 La3Zr 1.75 Ta 0.25 Al 0.2 O 12 , Li 6.15 La3Zr 1.75 Ta 0.25 Ga 0.2 O 12 , Li 6.25 La3Zr2Ga 0.25 O 12 , Li 6.4 La3Zr 1.4 Ta 0.6 O 12 , Li 6.5 La3Zr 1.75 Te 0.25 O 12 , Li 6.75 La3Zr 1.75 Nb 0.25 O 12 , Li 6.9 La3Zr 1.675 Ta 0.289 Bi 0.036 O 12 , Li 6.46 Ga 0.23 La3Zr 1.85 Y 0.15 O 12 , Li 6.8 La 2.95 Ca 0.05 Zr 1.75 Nb 0.25 O 12 , Li 7.05 La 3.00 Zr 1.95 Gd 0.05 O 12 , Li 6.20 Ba 0.30 La 2.95 Rb 0.05 Zr2O 12 and the like.

[0023] Garnet-type solid electrolytes are preferably those containing Mg and at least one of element A (where A is at least one element selected from the group consisting of Ca, Sr, and Ba), with the molar ratio of each element satisfying all of the following conditions (1) to (3), or those containing both Mg and element A, with the molar ratio of each element satisfying all of the following conditions (4) to (6). Element A is preferably Sr in order to increase the ionic conductivity of the solid electrolyte. (1) 1.33 ≤ Li / (La+A) ≤ 3 (2) 0 ≤ Mg / (La+A) ≤ 0.5 (3) 0 ≤ A / (La + A) ≤ 0.67 (4) 2.0 ≤ Li / (La+A) ≤ 2.6 (5) 0.01 ≤ Mg / (La+A) ≤ 0.14 (6) 0.04 ≤ A / (La + A) ≤ 0.17

[0024] Let's return to Figure 1 for explanation. The raw material powder 10 is set so that the proportion of metal elements matches or approximates the stoichiometric composition to the extent that the desired solid electrolyte can be obtained. The raw material powder 10 may contain certain metal elements that tend to evaporate and disappear during calcination in excess of the stoichiometric composition, such as lithium. The means of mixing the powders containing Li, La, and Zr can be wet or dry without limitation. Examples of the raw material powder 10 include powder, and molded bodies formed by applying pressure to the powder or agglomerating the powder.

[0025] The raw material powder 10 is fired in a firing jig 12 (refractory container). The firing jig 12 includes a base 13 and a lid 14. The lid 14 rests on the base 13 on which the raw material powder 10 is placed. By covering the base 13 with the lid 14 during firing, the evaporation of lithium contained in the raw material powder 10 and the inclusion of refractory materials or other materials falling from the furnace (not shown) can be reduced.

[0026] A hole 16 is provided in the lid 14 that connects the internal space 15 of the firing jig 12 to the outside of the firing jig 12. The gas generated by the thermal decomposition of the raw material powder 10 escapes to the outside of the firing jig 12 through the hole 16.

[0027] Examples of materials for the firing jig 12 include inorganic materials such as alumina, cordierite, mullite, silica, magnesia, and zirconia, and metallic materials whose main component is at least one of W, Mo, and Ni. "Main component" means that the combined mass of W, Mo, and Ni is 50 wt% or more of the mass of the metallic material.

[0028] Examples of metallic materials with W as the main component include W, W-Fe alloy, W-ThO2 alloy, W-Mo alloy, W-Zr alloy, W-Ni-Cu alloy, W-Ni-Mo alloy, W-Ni-Fe alloy, W-Ni-Fe-Mo alloy, and W-Ni-Cu-Fe alloy. Examples of metallic materials with Mo as the main component include Mo, Mo-Cu alloy, Mo-Zr-Hf-C alloy, Mo-La2O3 alloy, and Mo-Re alloy. Examples of metallic materials with Ni as the main component include Ni, Ni-Cu alloy, Ni-Mo-Fe alloy, and Ni-Fe alloy.

[0029] The firing temperature of the raw material powder 10 is exemplified as being between 850°C and 1200°C. The firing process may include a step of firing at a lower temperature and a step of firing at a higher temperature within this temperature range. The firing time is exemplified as being between 10 and 20 hours at the set maximum temperature.

[0030] Firing can be carried out while an atmospheric gas is flowing through the furnace. Examples of atmospheric gases include air-modified gases such as purified gas obtained by removing carbon dioxide from air, inert gases such as argon and helium, neutral gases such as nitrogen and ammonia, and reducing gases such as hydrogen and carbon monoxide.

[0031] The calcination of the raw material powder 10 is carried out under a steam atmosphere, in which steam is introduced into the solid-phase reaction field of the raw material powder 10. Examples of calcination under a steam atmosphere include supplying a steam-containing atmospheric gas to the raw material powder 10, and placing the moisture-containing raw material powder 10 inside a calcination jig 12. The moisture content of the raw material powder 10 inside the calcination jig 12 at room temperature is typically 1-20 wt% relative to the mass of the raw material powder 10 in order to promote reactions within or between solids. The moisture content of the raw material powder 10 inside the calcination jig 12 at room temperature is 4500-90000 g / m³ relative to the volume of the space 15 inside the calcination jig 12 (including the space occupied by the raw material powder 10). 3 Examples are given.

[0032] When the raw material powder 10 containing moisture is placed inside the firing jig 12 and fired, some of the water vapor inside the firing jig 12 escapes to the outside of the firing jig 12 through the holes 16. However, since the water vapor is present in the solid-phase reaction field of the raw material powder 10, the reactions within or between solids of the raw material powder 10 are promoted.

[0033] Examples of methods for impregnating the raw material powder 10 with water include using a liquid containing pure water as a medium for wet mixing of the powder, and mixing the powder with a liquid containing pure water and then separating the powder from the liquid. The moisture content of the raw material powder 10 can be adjusted by adjusting the temperature and time for drying the water-impregnated powder. The moisture content of the raw material powder 10 can be determined by the loss on drying method.

[0034] The raw material powder 10 after firing may be removed from the firing jig 12, pressure may be applied to the removed raw material powder 10 to form a molded body, and the molded body may be placed in the firing jig 12 and fired again. The firing temperature and time at this time are the same as the firing temperature and time for the raw material powder 10. Alternatively, the raw material powder 10 after firing may be removed from the firing jig 12, the removed raw material powder 10 may be crushed and mixed, and then fired again.

[0035] The fabricated solid electrolytes can be used as materials for energy storage devices such as secondary batteries and electrochemical capacitors. Examples of electrochemical capacitors include redox capacitors that utilize redox reactions and hybrid capacitors, which are asymmetric cells combining electric double-layer capacitors and solid electrolytes. Examples of materials for energy storage devices include sintered solid electrolytes, mixtures of solid electrolytes and electrolyte solutions, and slurries containing solid electrolytes and dispersion media.

[0036] The second embodiment will be described with reference to Figure 3. In the first embodiment, the case in which the space 15 inside the firing jig 12 is made into a steam atmosphere was described. In the second embodiment, the case in which the inside of the furnace 20 is made into a steam atmosphere will be described. In the second embodiment, the same reference numerals are used for the same parts as in the first embodiment, and some of the following descriptions will be omitted.

[0037] Figure 3 is a schematic diagram of the firing process in the second embodiment. The furnace 20 for firing the raw material powder 10 is a continuous firing furnace or a batch firing furnace. Firing can be performed while an atmospheric gas is flowing through the furnace 20. Pump 21 supplies water to evaporator 22, and evaporator 22 converts the water into steam. The atmosphere inside the furnace 20, into which the steam heated by evaporator 22 is introduced, becomes a steam atmosphere of 1 atmosphere. By bubbling an atmospheric gas (carrier gas) such as an inert gas or neutral gas in water in a constant temperature bath (not shown) and introducing it into the furnace 20, the partial pressure of steam inside the furnace 20 can be controlled.

[0038] In order to promote the reaction within or between solids of the raw material powder 10 during firing, steam is introduced into the furnace 20 until the temperature around the raw material powder 10 in the furnace 20 reaches at least 500°C. For example, 4500-90000 g / m³ relative to the volume of the furnace 20. 3 The raw material powder 10 is calcined while supplying a certain amount of steam. After the temperature inside the furnace 20 exceeds 500°C, the introduction of steam may be stopped, or steam may be continued to be introduced into the furnace 20. [Examples]

[0039] The present invention will be described in more detail by reference to examples, but the present invention is not limited to these examples.

[0040] (Example 1) Li 6.95 Mg 0.15 La 2.75 Sr 0.25 Zr 2.0 O 12 The raw materials for LLZ, Li2CO3, MgO, La(OH)3, SrCO3, and ZrO2, were weighed accordingly. Li2CO3 was kept in excess by approximately 15 mol% in elemental terms, considering the volatilization of Li during calcination. The specific surface area of ​​Li2CO3 is 1.2 m². 2 The specific surface area of ​​La(OH)3 is 11.3 m² / g. 2 The specific surface area of ​​ZrO2 is 22.2 m² / g. 2 The result was / g. The specific surface area of ​​the raw material powder was measured in accordance with JIS R1626:1996. The weighed raw material powder was mixed in a dry mixer for 0.5 hours.

[0041] 300g of raw material powder was placed in a mold, and a pressure of 1.6 MPa was applied to the raw material powder using a tabletop press (single-axis molding machine) to obtain a rectangular hexahedron molded body measuring 8cm in length, width, and height, and 4cm in thickness. The molded body was placed in a firing jig, which included a magnesia base, and the molded body (raw material powder) contained in the firing jig was fired in a furnace (batch firing furnace) with nitrogen gas flowing through it. The firing process was carried out at a rate of 600g / m² from room temperature to 500°C. 3 The temperature was raised to 1100°C while steam was flowing through it, and the firing jig was left in the 1100°C atmosphere for 10 hours before being cooled to room temperature.

[0042] (Example 2) A molded body of raw material powder was obtained in the same manner as in Example 1, except that the weighed raw material powder was mixed for 15 hours in a wet mixer using pure water as the medium, and then dried in a dryer at 120°C until the moisture content was 10 wt% (30 g of water). The moisture content of the raw material powder was adjusted by adjusting the drying time. The volume was 665.5 cm³. 3 The molded body was placed in the firing jig, and without introducing steam into the furnace, the molded body (raw material powder) was fired in a furnace through which nitrogen gas was flowed, in the same manner as in Example 1.

[0043] (Example 3) The weighed raw material powder was mixed in a dry mixer for 0.5 hours, and then immersed in pure water. The molded body was fired in the same manner as in Example 2, except that the raw material powder was dried in a dryer at 120°C until the moisture content of the raw material powder separated from the pure water was 1 wt% (3 g of water).

[0044] (Example 4) The molded body was fired in the same manner as in Example 3, except that the raw material powder was dried in a dryer at 120°C to a moisture content of 5 wt% (water content of 15 g).

[0045] (Example 5) The specific surface area of ​​Li2CO3 is 0.05 m². 2 The molded body was fired in the same manner as in Example 1, except that the weight was / g.

[0046] (Example 6) The specific surface area of ​​La(OH)3 is 2.7 m². 2 The molded body was fired in the same manner as in Example 1, except that the weight was / g.

[0047] (Example 7) The specific surface area of ​​ZrO2 is 9.2 m². 2 The molded body was fired in the same manner as in Example 1, except that the weight was / g.

[0048] (Comparative example) The molded body was fired in the same manner as in Example 1, except that steam was not introduced into the furnace.

[0049] (Powder X-ray diffraction) The molded bodies, after firing, were crushed using a mortar and pestle in a glove box under an argon atmosphere to prepare samples for powder X-ray diffraction. After obtaining the X-ray diffraction pattern of the samples using powder X-ray diffraction with CuKα rays, the X-ray diffraction pattern was analyzed using the Rietveld method to determine the proportion of cubic crystals.

[0050] It is known that the ionic conductivity of LLZ in the cubic crystal structure is higher than that of the tetragonal crystal structure. Since the cubic crystal structure of LLZ is the desired crystal structure and the tetragonal crystal structure is the undesirable crystal structure, samples with a cubic crystal proportion greater than 90 mass% (cubic:tetragonal = 90:10) were classified as A, samples with a cubic crystal proportion between 80 mass% and 90 mass% were classified as B, and samples with a cubic crystal proportion less than 80 mass% were classified as C. The results are shown in Table 1.

[0051] [Table 1]

[0052] In Examples 1, 5-7, the raw material powder was calcined while steam was introduced into the furnace, and in Examples 2-4, the raw material powder containing water was calcined in a calcination jig. In these examples, the raw material powder was calcined in a steam atmosphere, while in the comparative example, no steam was introduced during calcination. As shown in Table 1, Examples 1 and 7 received a rating of A or B, while the comparative example received a rating of C. In Examples 1 and 7, where the raw material powder was calcined in a steam atmosphere, a liquid phase was more easily formed on the surface of the raw material powder compared to the comparative example, and it is presumed that the decomposition of the raw material powder and the synthesis of LLZ proceeded more rapidly. As a result of the accelerated solid-phase reaction, it is presumed that the proportion of cubic crystals increased in Examples 1 and 7.

[0053] Examples 1-4 received a rating of A, while Examples 5-7 received a rating of B. In Examples 1-4, the specific surface area of ​​lithium carbonate was 0.10 m². 2 The value is 1 / g or more, and the specific surface area of ​​lanthanum hydroxide is 3.0 m². 2 The specific surface area of ​​zirconium oxide is 10.0 m² or more, and the specific surface area of ​​zirconium oxide is 10.0 m² or more. 2 The values ​​were 1 / g or higher. Compared to Examples 1-4, Example 5 had a smaller specific surface area of ​​lithium carbonate, Example 6 had a smaller specific surface area of ​​lanthanum hydroxide, and Example 7 had a smaller specific surface area of ​​zirconium oxide. In Examples 1-4, the specific surface area of ​​the raw material powder was larger than in Examples 5-7, so it is presumed that the decomposition of the raw material powder and the synthesis of LLZ proceeded faster, resulting in an even larger proportion of cubic crystals.

[0054] Although the present invention has been described above based on embodiments, it can be easily inferred that the present invention is not limited in any way to the above embodiments, and that various improvements and modifications are possible without departing from the spirit of the present invention. The shape and size of the firing jig 12 described in the embodiments are just examples.

[0055] In the examples, we have described a case in which a rectangular hexahedron molded body formed by applying pressure to the raw material powder 10 is fired, but this is not necessarily the only method. It is certainly possible to fire the raw material powder 10 by placing it in a crucible or other container (firing jig). [Explanation of Symbols]

[0056] 10 Raw material powder

Claims

1. A method for producing a solid electrolyte, comprising a calcination step for synthesizing a solid electrolyte having a garnet-type crystalline structure containing Li, La, Zr, and O, The aforementioned firing step is carried out under a steam atmosphere to produce a solid electrolyte.

2. The method for producing a solid electrolyte according to claim 1, wherein the raw material powder for synthesizing the solid electrolyte in the calcination step comprises lithium carbonate and lanthanum hydroxide.

3. The specific surface area of ​​the lithium carbonate is 0.10 m². 2 The amount is 1 / g or more, and the specific surface area of ​​the lanthanum hydroxide is 3.0 m². 2 A method for producing a solid electrolyte according to claim 2, wherein the amount is 1 / g or more.

4. The aforementioned raw material powder further contains zirconium oxide, The specific surface area of ​​the aforementioned zirconium oxide is 10.0 m². 2 A method for producing a solid electrolyte according to claim 2 or 3, wherein the amount is 1g or more.

Citation Information

Patent Citations

  • Manufacturing method of solid electrolyte, and solid electrolyte

    JP2019006634A